2010
DOI: 10.1002/asi.21401
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of Flickr tags and index terms in a general image collection

Abstract: Web 2.0 and social/collaborative tagging have altered the traditional roles of indexer and user. Traditional indexing tools and systems assume the top-down approach to indexing in which a trained professional is responsible for assigning index terms to information sources with a potential user in mind. However, in today's Web, end users create, organize, index, and search for images and other information sources through social tagging and other collaborative activities. One of the impediments to user-centered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 56 publications
1
49
0
4
Order By: Relevance
“…These 'folksonomies' (i.e., taxonomies defined by ordinary people) tend to be more flexible, scalable, decentralised, and easier to maintain than more formal classification schemas and ontologies, but su↵er from semantic incoherence, idiosyncratic usage of tags, as well as polysemy and synonymy, limiting the tags' informational value. (Rorissa 2010). All of these aspects converge in OSM, described in the next section.…”
Section: Semantic Negotiation In Crowdsourced Cartographymentioning
confidence: 92%
See 1 more Smart Citation
“…These 'folksonomies' (i.e., taxonomies defined by ordinary people) tend to be more flexible, scalable, decentralised, and easier to maintain than more formal classification schemas and ontologies, but su↵er from semantic incoherence, idiosyncratic usage of tags, as well as polysemy and synonymy, limiting the tags' informational value. (Rorissa 2010). All of these aspects converge in OSM, described in the next section.…”
Section: Semantic Negotiation In Crowdsourced Cartographymentioning
confidence: 92%
“…Contributors often disagree on the conceptual granularity, which is the level of detail to be included in the conceptualisation. To understand this aspect, a useful distinction can be drawn from cognitive psychology applied to folk taxonomies, following Rorissa (2010). According to a seminal categorisation theory by Rosch (1999), abstract concepts belong to the superordinate level (e.g., furniture), while concrete concepts are located at the basic level (e.g., chair).…”
Section: Granularity Negotiation and Infinite Knowledgementioning
confidence: 99%
“…For example, in a comparison of Flickr tags and index terms from the University of St. Andrews Library Photographic Archive, Rorissa stresses the importance of exploring similarities and differences between indexers' and users' language, noting that "social tagging could serve as a platform on which to build future indexing systems." 26 Like others, Rorissa hopes that continued research into user-generated social tags will be able to "bridge the semantic gap between indexerassigned terms and users' search language." 27 In fact, some are currently utilizing social tags in an effort to describe and facilitate access to collections.…”
Section: User-generated Tags and Traditional Metadatamentioning
confidence: 97%
“…Heymann et al investigated a large-scale sample of forty million bookmarks from the social bookmarking site del.icio.us and found that in 20% of the cases user tags do not occur in the page text, backlink page text, or forward link page text of the pages they annotate. Studies in (Bischoff et al, 2004a;Halvey et al, 2007;Rorissa, 2010;Yanbe et al, 2007) investigate this phenomenon across multiple domains and multimedia resource types and identify the gaps between the tag space and the querying vocabulary. The common conclusion is that user tags can improve search by bridging the vocabulary gap.…”
Section: Related Workmentioning
confidence: 99%